2015
DOI: 10.5539/gjhs.v8n6p109
|View full text |Cite
|
Sign up to set email alerts
|

Needs of Hemodialysis Patients and Factors Affecting Them

Abstract: Purpose:Of this study was to explore the needs of hemodialysis patients and the factors that affect them.Material & Methods:The sample of the study included 141 patients undergoing hemodialysis. Data collection was performed by the method of interview using a specially designed questionnaire which served the purposes of the study. The needs were grouped into six categories. Patients were asked to answer how important was for them each of the statements in the questionnaire. Furthermore, there were collected so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 20 publications
2
26
0
4
Order By: Relevance
“…According to patients’ reports, they mainly desire psychological, social, and spiritual support (1) while the needs for support are associated with age, education level, place of residence, difficulties in relations with family members and anxious personality (12). However, the needs for social support vary among patients undergoing hemodialysis that is mainly attributed either to the quality and quantity of their social network or to the severity of the disease (11).…”
Section: Introductionmentioning
confidence: 99%
“…According to patients’ reports, they mainly desire psychological, social, and spiritual support (1) while the needs for support are associated with age, education level, place of residence, difficulties in relations with family members and anxious personality (12). However, the needs for social support vary among patients undergoing hemodialysis that is mainly attributed either to the quality and quantity of their social network or to the severity of the disease (11).…”
Section: Introductionmentioning
confidence: 99%
“…The present study showed that very informed were patients below 40 years old or those aged 41-50 years old. According to a prior study by Xhulia et al, ( 7 ) who explored the needs of 141 hemodialysis patients, the need of information was important to patients aged 61-80 years old. Possibly health professionals pay more attention on younger patients between 30 and 45 years of age, who still maintain their ability to cope with their life situation ( 8 ) though their aspirations are often constrained by illness ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…The higher scores for depression in Cluster 1 might be explained by the significantly older age of participants compared to Cluster 2. Although age has been shown to play a role in emotional needs of hemodialysis patients [26], whether these needs are related to depression will require further studies.…”
Section: Hope Depression and Symptom Disturbance For Hemodialysis Pmentioning
confidence: 99%
“…Understanding the demands of hemodialysis patients could help these patients cope with this chronic disease and help nurses provide appropriate support to increase hope. Studies have examined the demands of family members of dialysis patients [26] and the general needs of dialysis patients [27]. However, demands of patients may vary with age, severity of physical symptoms, and psychological state.…”
Section: Introductionmentioning
confidence: 99%